Generation and wired/wireless transmission of IEEE802.16m signal using solitons generated by microring resonator - Alavi, Sayed Ehsan (Springer, 2015)
Multi-carrier generation is the main building block for generating WiMax signal. In order to use WiMax signal in radio over fiber applications the use of all optical generation of RF signals is required. To generate multi carriers optically, the system consisting of series of microring resonators (MRRs) incorporating with an add/drop filter system are used. Thus the high frequency (THz) solitons range of 193.29–193.35 THz at frequencies of 193.333, 193.3355 and 193.3388 THz with the free spectral range of 2.5 and 5.8 GHz could be performed using MRRs, providing required WiMax signal used in wired/wireless communication. The generated multi carriers are multiplexed with the single carrier soliton and transmitted through single mode fiber (SMF) after being beaten to photodiode, a WiMax signal is propagated wirelessly in transmitter antenna base station and is received by the second antenna located in the receiver. Here, based on the switching of channel 1 or channel 2, the 2.5 or 5.8 GHz RF WiMax can be generated. When the RF signal is up-converted at the receiver central office, the detected signal is analysed in order to evaluate the error vector magnitude (EVM) of each wireless channel. As results, both channels show a soft EVM variation for different path lengths, where the transmission of both channels is feasible for up to a 50 km SMF path length